Perlis floods 2005/2010: Astudy on cause and flood management at Kampung Titi Besi, Arau - Nor Liyana Binti Abdul Rahim (School of Environmental Engineering, University Malaysia Perlis, 2011)
Flood management is based on the cause of flood. Flood had happened in Perlis in 2005 and 2010. Thus, two cause of flood that will be discuss in this reseacrh is rainfall and land use. It is to evaluate whether rainfall or land use is the main cause of the flood in Perlis. The analysis is done by observing , interviewing the flood victim and related people, and site viist to study area. Understanding of flood behaviors required spatial and numerical approaches. This research discusses data analysis using Storm Water Management Model 5 (SWMM5) to stimulate the flood water of Sungai Arau at Kuala Tunggang Station located at Arau, Perlis.